PENGARUH PERBEDAAN KONSENTRASI GELATIN CEKER AYAM KAMPUNG TERHADAP KARAKTERISTIK FISIK EDIBLE FILM - Asmudrono, Sukma W.; Sompie, M.; Siswosubroto, S.E.; Kalele, J.A.D. (Universitas Sam Ratulangi, 2019)
THE EFFECT OF DIFFERENCES CONCENTRATION OF NATIVE CHICKEN CLAW GELATIN ON THE PHISYCAL CHARACTERISTICS OF EDIBLE FILM. This study aims to determine the effect of differences concentration on the physical characteristics of edible film from native chicken claw gelatin. This study used a completely randomized design with the treatment of chicken claw gelatin concentration 5%, 10%, 15 and 20%, each treatment repeated four times. The results showed that the differences concentration of native chicken claw gelatin had significantly different effect (P<0.05) on the value of tensile strength, elongation and thickness of edible film. Based on the results of discussion, it can be concluded that the concentration of native chicken claw gelatin from variables with 10% gelatin concentration had good physical characteristics of edible film.Â Keywords: Native chicken claw, Edible film Gelatin